Kontekstualisme Problematika Pembelajaran Agama Islam Pada Masa Pandemi Covid-19 - Eva Yulianti (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
The contextualism of learning problems during the pandemic in today's society, some parents of participants do not have mobile devices (Android) or computers to support online learning, especially for students themselves. Such conditions make them confused in facing the existing reality. One side is faced with the lack of supporting facilities, on the other hand there is a demand for the fulfillment of educational services for students. Learning Islamic religious education through online learning requires reflection and separate thoughts which in the process require role models (uswatun khasanah) in the process of transferring the values ??of Islamic education which are problematic in its implementation. The purpose of this paper is to examine how the Problems of Islamic Learning During the Covid-19 Pandemic, so that the results of this study are expected to be material for information and reference in making policies in implementing online learning, both for teachers, students, schools, parents and the government. The results of this study indicate that 1) The change of conventional learning systems to online systems suddenly (due to the Covid-19 pandemic) without careful preparation. Finally, some teachers are not able to keep up with changes with information and technology-based learning. 2) The problems experienced by parents in accompanying children to study at home include a lack of understanding of the material by parents, difficulties for parents in fostering children's interest in learning, not having enough time to accompany children because they have to work, parents are impatient in accompanying children while studying at home, difficulties of parents in operating gadgets, and constraints related to internet service coverage. 3) Learning must take place not only to provide information or knowledge, but must touch the heart, liberate, and enlighten. Islamic religious education learning, besides aiming to strengthen beliefs, must also be oriented to instill empathy, sympathy, and solidarity with others. Learning Islamic Religion must touch multicultural Islamic education, namely Islamic values ??that uphold the spirit of respecting differences and synergize for progress and love peace and social justice. The kyai, ustadz, teachers in Islamic boarding schools and Islamic education institutions in general, should provide a good example (uswatun hasanah) without violence in preaching and rely on the spirit of fastabiqu al-khayrat.